Effective Nurse Communication on The Level of Client Satisfaction in The Inpatient Room - Noor Amaliah; Dessy Ana Anggraini; Iswantoro Iswantoro (MBUnivPress, 2022)
One of the factors that influence patient satisfaction with health services is communication by health workers. The implementation of nursing care is never separated from the interaction process that occurs between nurses and clients because nursing is based on a caring and helping relationship, in this relationship good communication is needed. Effective communication and quality of nursing services are factors that contribute to patient satisfaction. Clients as users of nursing services demand nursing services in accordance with their rights, namely quality and complete nursing services. Clients will complain if the perceived caring behavior does not provide satisfaction for him. Objective: To determine the relationship between effective nurse communication and the level of client satisfaction in the Inpatient Room. Methods: The design of this study was correlational with a cross sectional approach. The population in this study were clients who were treated in an inpatient room, totaling 20. Random sampling technique, the sample in this study was 17. Spearman's Rho correlation test with = 0.05. Results: In this study 14 respondents (82.4%) implemented effective communication and 3 respondents (17.6%) had not/less implemented effective communication and 14 respondents (82.4%) were satisfied and 3 respondents (17.6%) ) not satisfied. The results of the Spearman's Rho Correlation Test obtained p value = 0.000. The conclusion of the correlation between effective communication with client satisfaction is significant. With the Spearman Correlation value of 0.835, it shows that there is a relationship between effective nurse communication and the level of client satisfaction in the inpatient room.